Sluicing in Basque: a move-and-delete analysis - Macazaga Núñez, Irene (Fontes linguae vasconum, 2024)
In this paper I explore sluicing in Basque, the elliptical phenomenon whereby the interrogative clause is elided, but the wh-remnant is pronounced. Specifically, I address the long-debated question of whether sluicing involves a full-fledged syntactic structure or not. By employing diverse cross-linguistic tests (case matching, binding, and adposition (non-)stranding), I show that there is structure therein. In short, I entertain the hypothesis that this phenomenon involves independently available wh-movement and subsequent deletion of the ellipsis site, which consists of silent structure; namely, I propose a move-and-delete account for sluicing in Basque.